Sewage Pollution In Kelang River and its Estuary - Law, A. T. (1980)
High faecal coliform counts detected in Kelang River reveal that the River is being heavily polluted by domestic sewage discharge. The average faecal coliform counts in water from Stations I, II, III, IV, V and VI were 113/100 ml, 1 x 106 /100 ml, 1 x 105 /100 ml, 1.6 x 106 /100 ml, 5.8 x 103 /100 ml and 260/100 ml respectively. As compared to the WHO recommended guide limit of100 faecal califorms/100 ml for bathing water, counts in all stations except Station I were much higher than the recommended limit. The average concentration of faecal coliforms in sediment of Stations I, II, III and IV were 17.9/g, 1 x 104 /g, 3.2 x 104 /g and 1.6 x 104 /g respectively. The faecal coliform coun ts at the estuary ofKelang River were much lower than those of the coastal waters of Penang and Johore. The reason is not clear. Most probably the suspended solids play an important role in the disappearance of faecal coliforms in the estuary.